Anti‐JMH alloantibody in inherited JMH‐negative patients leads to immunogenic destruction of JMH‐positive RBCs. (13th June 2021) - Yuan, Zhaohu; Wei, Yaming; Chen, Xiaojie; He, Shufei; Cai, Kui; Zhong, Minglu; Huang, Huiying; Tong, Xinxin; Liu, Zhen; Yang, Xuexin
Summary: The clinical significance of the specific anti‐John Milton Hagen (JMH) alloantibody in inherited JMH‐negative patients remains unclear. During clinical blood transfusion, it is often classified as an anti‐JMH autoantibody in acquired JMH‐negative patients, which might further lead to the occurrence of haemolysis events. In this study, we found that the proportion of inherited JMH‐negative people in the Guangzhou population was 0.41%, based on the study of 243 blood samples by flow cytometry. Gene sequencing analysis revealed two novel variants located in exon 11 (c.1348G>A, p.Ala449Thr) and exon 14 (c.1989G>T, p.Leu663Phe). Specific antigen presentation showed that JMH‐positive RBCs (red blood cells) could be internalized by SEMA7A −/− dendritic cells (DCs) and that SEMA7A −/− DCs activated by the semaphorin 7a (Sema7a) protein or JMH‐positive erythrocytes further induced activation of CD4 + T cells to secrete interferon (IFN)‐γ. Transfusion of JMH‐positive RBCs could lead to the production of the specific anti‐JMH alloantibody in Sema7a knock‐out (KO) C57 mice. After erythrocyte sensitization, complement C3 was specifically fixed, causing the destruction of JMH‐positive erythrocytes. The anti‐JMH alloantibody caused immunological destruction of JMH‐positive erythrocytes and promoted the clearance of JMH‐positive RBCs. We should be cautious when making conclusions about the clinical significance of the anti‐JMH alloantibody. Abstract : 1. Specific antigen presentation showed that JMH‐positive RBCs could be internalized by SEMA7A −/− dendritic cells (DCs) and that SEMA7A −/− DCs activated by the Sema7a protein or JMH‐positive erythrocytes further induced activation of CD4 + T cells to secrete IFN‐γ.2. Transfusion of JMH‐positive RBCs could lead to the production of the specific anti‐JMH alloantibody in Sema7a KO C57 mice.3. The anti‐JMH alloantibody caused immunological destruction of JMH‐positive erythrocytes and promoted the clearance of JMH‐positive RBCs.